1999
DOI: 10.3109/01674829909075573
|View full text |Cite
|
Sign up to set email alerts
|

Repeat abortion: A qualitative study

Abstract: In a qualitative study of 20 women seeking a repeat abortion, interviews lasting for 1.5-2 hours were conducted after the first appointment with a gynecologist when the abortion was planned. The women were aged 20-29 years and had experienced one to five abortion(s) during the previous 5 years. The aim of the study was to attain understanding of the phenomenon of repeat abortion. The women were asked to express their thoughts related to their situation and their choices. The following categories were found: ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…37 These difficulties are not addressed during attendance at acute services and are compounded by the often judgmental treatment of services. 6,28,34…”
Section: Resultsmentioning
confidence: 99%
“…37 These difficulties are not addressed during attendance at acute services and are compounded by the often judgmental treatment of services. 6,28,34…”
Section: Resultsmentioning
confidence: 99%
“…Research has been done to explore the social, psychological and ethnic profiles of women undergoing repeat terminations (Ertopcu et al 2005;Fisher et al 2005;GarciaHernandez et al 2000;Tornbom and Moller 1999). The Department of Health published the national sexual health and HIV strategy in July 2001 to improve sexual health services (DoH 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Findings from the current study offer further support for this, as levels of sexual problems were higher in relationships that subsequently ended. In fact, the number of relationships that had ended by the time of the pre-abortion meeting in this study (23%) could reflect the finding that the main motivation for having an abortion is due to problems within the relationship (Holmgrem, 1994;Tornbom et al, 1996, in Tornbom & Moller, 1999. Finally, it could also be suggested that the increase in sexual problems was due to physical or biological changes associated with early pregnancy that had nothing to do with the decision to have an abortion.…”
Section: Sexual Problemsmentioning
confidence: 51%